Cyber-Terrorism in The Context of Proselytizing, Coordination, Security, and Mobility - Ramadhan, Iqbal (Universitas Muhammadiyah Yogyakarta, 2020)
The simplicity and flexibility of information and technology have made human life much easier. Terrorist groups nowadays have been using these things to disseminate terror, recruit new members, fundraise, and mobilize their activities. Technology provides terrorist group a leverage to conduct its hideous activity. Globalization eventually gives the double-edge sword that needs to be addressed by state actor regarding terrorist issues. The author used James D. Kiras’ four concepts of cyber-terrorism such as proselytizing, coordination, security, and mobility. Those four concepts are harnessed by terrorist group in modern world to achieve their interest. On the other side, the author harnessed comprehensive security from the Copenhagen School of Security Studies to analyze the threat which came from cyber-terrorism activity. The aim of this article is to analyze terrorist groups in conducting their activity based on Kiras’ four concepts of cyber-terrorism. By using Kiras’ concept in Comprehensice Security from Copenhagen School, the author aims to analyze the impact of cyber terrorism both on state and society. The author also used qualitative method as analytical tools to analyze the research problem. The author concluded that the state had to establish a rigid counter-terrorism system holistically at the domestic level without neglecting international strategic cooperation among international actors to counter this threat. Keywords: Cyber-terrorism, proselytizing, coordination, security, mobility.